Towards Sustainable Dairy Production in Argentina: Evaluating Nutrient and CO2 Release from Raw and Processed Farm Waste - Iocoli, Gastón Alejandro; Orden, Luciano; López, Fernando M.; Gómez, Marisa A.; Villamil, María B.; Zabaloy, María C. (MDPI, 2022)
Mineralization studies are the first step in determining the usefulness of an amendment such as fertilizer, and are essential to creating guidelines for dairy waste management to help producers make informed decisions. Our goal was to assess the effects of dairy raw, composted, and digested manure amendments on C, N, and P mineralization to evaluate the feasibility of their in-farm production and use as organic fertilizers. The liquid and solid fractions of dairy effluent (LDE, SDE), dairy effluent digestate (DED), onion–cattle manure digestate and compost (OCMD, OCMC) were characterized by chemical and spectroscopic methods. Soil microcosms with LDE, SDE, DED, OCMD and OCMC and the C, N and P mineralization were determined periodically. Elemental and structural differences among amendments led to contrasting profiles of C, N, and P mineralization, and thus to differences in nutrient availability, immobilization, and CO2 emission. All processed materials were more stable than untreated waste, reducing C emissions. Digestates showed net C immobilization, and supplied the highest levels of available N, creating a relative P deficit. Instead, the compost supplied N and P via mineralization, producing a relative P excess. Future studies should aim at evaluating fertilization strategies that combine both kinds of amendments, to exploit their complimentary agronomic characteristics.